Pengaruh Atribut, Citra, dan Layanan Dalam Membentuk Kepercayaan Pengunjung Agrowisata di Subak Jatiluwih Tabanan: Pengaruh Atribut, Citra, dan Layanan Dalam Membentuk Kepercayaan Pengunjung Agrowisata di Subak Jatiluwih Tabanan - Desak Gede Fitri Patricia; Ni Made Classia Sukendar (Journal Science Innovation and Technology (SINTECH), 2025)
Agrotourism of Subak Jatiluwih is an agrotourism located in Tabanan Regency, renowned for its unique terracing system and its preservation of traditional irrigation methods, which has been recognized as a UNESCO World Heritage Site since 2012. The purpose of this research is to (a) analyze the influence of attributes on visitor trust at Subak Jatiluwih Agrotourism; (b) analyze the influence of image in shaping visitor trust at Subak Jatiluwih Agrotourism; (c) analyze the influence of service quality in shaping visitor trust at Subak Jatiluwih Agrotourism. This study employs both qualitative and quantitative approaches through a survey method by distributing questionnaire to 100 visitors at Subak Jatiluwih Agrotourism. The data analysis technique used is Structural Equation Modeling with the SmartPLS 4.1.1 software. The result show that (a) agrotourism attributes significant effect on visitor trust; (b) the agrotourism image insignificant effect on visitor trust; (c) the quality of agrotourism services significant effect on visitor trust. Therefore, it is recommended to pay more attention to and improve the existing agrotourism image to influence visitor trust.